In Silico Assessment of Chemical Constituents of Zingiber officinale Rosc. For Anti-diabetic Activity: Molecular Docking with α-Glucosidase Receptor - Normi, Normi; Supandi, Supandi; Komala, Ismiarni (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Diabetes Mellitus (DM) is a disease in which blood sugar (glucose) levels are elevated because the body cannot release or utilize insulin adequately. Rhizome of Zingiber officinale Rosc. (ginger) has been reported to possess anti-diabetic properties. This study aimed to provide information on the chemical components of ginger that have potential in silico antidiabetic activity against the α-glucosidase receptor. Twenty chemical components of ginger (quercetin, catechin, humulene, β-sesquiphellandrene, camphene, farnesene, β-sitosterol, stigmasterol, curcumin, 6-gingerol, 8-gingerol, 10-gingerol, 6-shogaol, 8-shogaol, 10-shogaol, 6-paradol, 8-paradol, 10-paradol, methyl-6-gingerol, and methyl-8-gingerol) were used as ligands. An in silico study was conducted using the molecular docking technique with the AutoDock Vina software, which was then displayed using PyMOL and Biovia Discovery Studio. The grid box settings obtained in this study were as follows: center_x = -20.209, center_y = -6.763, center_z = 9.393, size_x = 12, size_y = 10, size_z = 12, and spacing (angstrom) = 1. The results indicated that the native ligand acarbose exhibited a binding energy of -6.9 kcal/mol. In contrast, four test ligands, quercetin (-7.3 kcal/mol), catechin (-7.1 kcal/mol), curcumin (-7.0 kcal/mol), and 6-gingerol (-7.0 kcal/mol) - demonstrated lower binding energies than acarbose, suggesting more stable conformations and more potent pharmacological effects. Lipinski analysis revealed that these four test ligands met all five Lipinski rule criteria. The study calculated the Root Mean Square Deviation (RMSD) value for the Docking of acarbose with the α-glucosidase macromolecule, resulting in a value of 0.384 Å. Interaction analysis conducted using Biovia Discovery Studio software revealed various interaction types, including hydrogen bonding, hydrophobic, electrostatic, and unfavorable interactions. In conclusion, this study provides valuable insights into potential therapeutic compounds derived from ginger and offers a foundation for further research and development in pharmaceutical and medicinal chemistry.